The Association Between 25-hyroxyvitmin D Concentration and Macronutrients Consumption with Obesity-related Variables in Korean Women (P18-062-19). (13th June 2019) - Doo, Miae; Wang, Chunyang; Jeon, Yoojin; Chun, Hyejin
Abstract: Objectives: Deficiency of vitamin D is increasing in worldwide and has been reported to be associated with chronic disease such as obesity, cardiovascular disease, and hypertension. The risk of vitamin D deficiency and chronic disease is related with higher prevalence after menopause. Methods: Using a cross-sectional study of 8726 Korean women, this study was investigated combined interaction effect of vitamin D concentration and dietary macronutrients consumption on obesity-related variables in relation to menopausal status. Results: The percentage of vitamin D insufficient (vitamin D < 50 nmol/L) in premenopausal and postmenopausal women was 84.5% and 67.7%, respectively. The subjects with vitamin D insufficient group had higher obesity-related variables such as BMI ( P  = 0.019), FG ( P  = 0.019), TG ( P  < 0.001), and HDL-C ( P  = 0.006) than those in the vitamin D sufficient group (vitamin D ≥ 50 nmol/L). The interaction effect of menopausal status and vitamin D concentration on obesity-related variables significantly differ. The subjects with vitamin D insufficient group among postmenopausal women had higher BMI ( P  < 0.001), waist circumference ( P  = 0.011), fasting glucose ( P  = 0.035) and triglycerides ( P  = 0.001) compared to those with sufficient group. Also, among only postmenopausal women, the subjects who were vitamin D insufficient, the risk of obesity was significantly increased by 1.1297 (95% CI = 1.078–1.560) using the vitamin D sufficient as reference. However, the obesity-related variables and risk of obesity according to vitamin D concentration did not differ among premenopausal women. Moreover, among the subjects with a low dietary protein consumption, the subjects in vitamin D deficient had an increasing trend in the risk of obesity by 1.308 times (95% CI = 1.039–1.647) than those with sufficient group. However, those findings did not differ among premenopausal women. Conclusions: Thus, the risk of obesity due to vitamin D deficient in postmenopausal women may be modified by the consumption of dietary protein. Funding Sources: This study was supported by the research funds of Kunsan National University and the Basic Science Research Program of the National Research Foundation of Korea (NRF) funded.